Effect of Aqueous Extracts of Arum cyreniacum on Some Negative and Positive Gram bacteria. - Abdulrraziq, Ahmed Amrajaa; Salih , Sami Mohammed (Al-Mukhtar Journal of Sciences, 2020)
The naming of Arum cyreniacum is associated with Cyrenaica province, its native and only region, especially Al-Jabal Al-Akhdar region. It's considered one of the well-known plants used in the past for food and medical purposes, and given the recent trend towards the use of medicinal plants in the field of biological control, this study aimed to test the inhibitory efficacy of cold and hot aqueous extracts of Arum using several concentrations (100, 200, 300, 400) mg/ml against three species of negative gram bacteria (Escherichia coli, Proteus vulgaris, Pseudomonas aeruginosa), and two species of positive gram bacteria (Staphylococcus aureus, Bacillus sp.) which are known to be pathogenic in humans, and compare it with Tetracycline using agar well diffusion method. The obtained results indicated that the tested aqueous extracts of Arum cyreniacum showed a clear inhibition effect towards the growth of the tested bacteria. The concentration of 400 mg/ml was recorded as being the most effective in exhibiting inhibition compared to other concentrations of extracts and the antibiotic ranging between (8.2-15) mm. Meanwhile, the concentration of 100 mg/ml showed no inhibitory effects with all species of bacteria except Bacillus sp., On the other hand, Escherichia coli and Pseudomonas aeruginosa were the most resistant to the antibiotic. The results also showed that the high efficiency of the cold extract was with negative bacteria and with positive bacteria for the hot extract